Upaya Meningkatkan Aktivitas dan Hasil Belajar Bahasa Arab Pada Materi At-Ta’aruf Bi Nafsi Melalui Penerapan Model Bertukar Pasangan Siswa Kelas VII-2 MTsN 8 Aceh Besar Tahun Pelajaran 2018/2019 - Marliah, Marliah (Yayasan Darul Hasanah Aceh, 2025)
The purpose of this study is to improve the activities and learning outcomes of Arabic in the At-Ta'aruf Bi Nafsi material for grade VII-2 MTsN 8 Aceh Besar students for the 2018/2019 Academic Year. The model used in this class action research is a learning model of exchanging pairs. The subjects of this class action research are students of class VII-2 MTsN 8 Aceh Besar in the 2018/2019 Academic Year. The number of students is 34 students with 19 male students and 15 female students. This class action research was conducted in the 2018/2019 academic year. This class action research was carried out within a period of 3 months, from September to November 2018 in odd semesters. The methodology of this study is that classroom action research consists of two cycles and each cycle consists of two meetings. Each cycle consists of planning, execution, observation and reflection. The research procedure consists of pre-research, one-cycle planning, one-cycle action execution, one-cycle observation, one-cycle reflection, two-cycle planning, two-cycle action execution, two-cycle observation and second-cycle reflection. The data collection technique is to collect test scores that are carried out at the end of each learning in each cycle using a question instrument (written test). Observation data is carried out by looking at the activeness of students in the learning process. The data are analyzed by means of percentage statistics. The results showed that in the pre-cycle 58.82% increased to 70.59% in cycle I and in cycle II to 91.18%. Student learning activities have increased from the enough to good category and the good category increased to excellent. The application of the pair exchange model can improve Arabic learning activities and outcomes in the At-Tarif Bin Nafsi material for grade VII-2 MTsN 8 Aceh Besar Academic Year 2018/2019.